2014
DOI: 10.1016/j.ophtha.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Optic Nerve Development in Preterm and Term Infants Using Handheld Spectral-Domain Optical Coherence Tomography

Abstract: Purpose Evaluate effects of prematurity on early optic nerve (ON) development and potential utility of ON parameters as indicators of central nervous system (CNS) development and pathology. Design Prospective cross-sectional and longitudinal study. Participants and Controls Forty-four preterm infants undergoing retinopathy of prematurity (ROP) screening and fifty-two term infants. Methods We analyzed optic nerves from portable handheld spectral domain optical coherence tomography (SDOCT) images (Bioptige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…However, the study suggests that gestational age, low weight at birth and gender may be more influential in the long term in these children, thus being necessary to monitor this population -as has been observed in other studies reviewed (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . These results evidenced the importance of monitoring these children from birth, although none of them followed-up on psychological factors such as those proposed by Kupfer et al (39) , indicated as closely related to language acquisition (40) .…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…However, the study suggests that gestational age, low weight at birth and gender may be more influential in the long term in these children, thus being necessary to monitor this population -as has been observed in other studies reviewed (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . These results evidenced the importance of monitoring these children from birth, although none of them followed-up on psychological factors such as those proposed by Kupfer et al (39) , indicated as closely related to language acquisition (40) .…”
Section: Discussionmentioning
confidence: 69%
“…When infants who suffered from retinopathy of prematurity were observed, one study found that premature infants with retinopathy at different levels had no association between hearing and speech scores at 3 years old on the Griffiths Mental Development Scales, but male infants with lower gestational age and low birth weight showed lower language performance (23) . Additionally, another study (20) did not find association between language scores on the Bayley Scales at 18 and 22 months old with other conditions related to the optical nerve. Three studies (13,24,26) investigated the association between language scores and white matter abnormalities in the neonatal period.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations